PENGARUH LEVERAGE, RMC DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN ERM - Sri Sudarsi; Widhian Hardiyanti; Andi Kartika (Jurnal Akuntansi dan Pajak, 2023)
Every business activity is always faced with unavoidable uncertainties. Business uncertainty that occurs usually follows the size of the business. The larger the size of a company, the greater the uncertainty that threatens it. Uncertainty in the business world is also known as a business risk. Unavoidable business risks make the company carry out risk control. Integrated and comprehensive risk control is one of the management strategies to create good corporate value in the eyes of stakeholders. This study examines the effect of leverage, risk management committee (rmc), and company size on enterprise risk management (erm) disclosures in manufacturing companies listed on the IDX from 2017 to 2020. This type of research is quantitative and uses a descriptive method. The sampling technique used purposive sampling and obtained as many as 70 companies. The data analysis method used is multiple linear regression analysis using the spss version 25 application. The research results show that leverage, rmc, and firm size have a significant simultaneous effect. Partially, leverage has no significant negative effect on erm, rmc has a positive and significant effect on erm, while firm size has no positive or significant effect.